Green Manufacturing Fundamentals and Applications - Dornfeld, David A. (Springer US : Imprint: Springer, 2013)
Green Manufacturing: Fundamentals and Applications introduces the basic definitions and issues surrounding green manufacturing at the process, machine and system (including supply chain) levels. It also shows, by way of several examples from different industry sectors, the potential for substantial improvement and the paths to achieve the improvement. Additionally, this book discusses regulatory and government motivations for green manufacturing and outlines the path for making manufacturing more green as well as making production more sustainable. This book also: • Discusses new engineering approaches for manufacturing and provides a path from traditional manufacturing to green manufacturing • Addresses regulatory and economic issues surrounding green manufacturing • Details new supply chains that need to be in place before going green • Includes state-of-the-art case studies in the areas of automotive, semiconductor and medical areas as well as in the supply chain and packaging areas Green Manufacturing: Fundamentals and Applications is an ideal book for graduate students, academic researchers, practicing engineers and scientists in the fields of mechanical engineering and industrial engineering interested in sustainable manufacturing and its applications.